Hyers Stability in Generalized Intuitionistic P-Pseudo Fuzzy 2-Normed Spaces - Ehsan Movahednia; Manuel De la Sen (Axioms, 2022)
In this article, we defined the generalized intuitionistic P-pseudo fuzzy 2-normed spaces and investigated the Hyers stability of m-mappings in this space. The m-mappings are interesting functional equations; these functional equations are additive for m = 1, quadratic for m = 2, cubic for m = 3, and quartic for m = 4. We have investigated the stability of four types of functional equations in generalized intuitionistic P-pseudo fuzzy 2-normed spaces by the fixed point method.